Matrix Equations In Reciprocal Cost Allocation: An Application In The Takaful Industry In Malaysia - Sharifah Fairuz Syed Mohamad; Syed Othman Alhabshi; Ahcene Lahsasna (Academic Inspired Network, 2024)
Indexed by MyCite